Digital Transformation and Innovation Performance in Small- and Medium-Sized Enterprises: A Systems Perspective on the Interplay of Digital Adoption, Digital Drive, and Digital Culture - Shaofeng Wang; Hao Zhang (Systems)
Small- and medium-sized enterprises (SMEs) face complex systemic challenges in managing digital transformation while pursuing innovation in an increasingly interconnected business environment. This study adopts a systems theory perspective to investigate how digitalization enhances Innovation Performance by examining the dynamic interrelationships among digital adoption, digital drive, digital culture, and Innovation Performance. Through an empirical analysis of 201 Chinese SMEs using PLS-SEM, IPMA, and ANFIS approaches, we reveal that digital drive fully mediates the relationship between digital adoption and Innovation Performance, highlighting the systemic nature of digital transformation processes. Digital culture emerges as a critical moderator, positively influencing the relationships between digital adoption and digital drive, as well as between digital drive and Innovation Performance. These findings demonstrate how different elements of digital transformation form an integrated system where components interact to produce innovation outcomes. This study contributes to systems theory by illuminating the complex interdependencies in digital transformation and offers practical implications for managing systemic change in SMEs.